Microphysical and radiative changes in cirrus clouds by geoengineering the stratosphere. Issue 10 (22nd May 2013) - Cirisan, A.; Spichtinger, P.; Luo, B. P.; Weisenstein, D. K.; Wernli, H.; Lohmann, U.; Peter, T.
Abstract: [1] In the absence of tangible progress in reducing greenhouse gas emissions, the implementation of solar radiation management has been suggested as measure to stop global warming. Here we investigate the impacts on northern midlatitude cirrus from continuous SO2 emissions of 2–10 Mt/a in the tropical stratosphere. Transport of geoengineering aerosols into the troposphere was calculated along trajectories based on ERA Interim reanalyses using ozone concentrations to quantify the degree of mixing of stratospheric and tropospheric air termed "troposphericity". Modeled size distributions of the geoengineered H2 SO 4 ‐H2 O droplets have been fed into a cirrus box model with spectral microphysics. The geoengineering is predicted to cause changes in ice number density by up to 50%, depending on troposphericity and cooling rate. We estimate the resulting cloud radiative effects from a radiation transfer model. Complex interplay between the few large stratospheric and many small tropospheric H2 SO 4 ‐H2 O droplets gives rise to partly counteracting radiative effects: local increases in cloud radiative forcing up to +2 W/m 2 for low troposphericities and slow cooling rates, and decreases up to −7.5 W/m 2 for high troposphericities and fast cooling rates. The resulting mean impact on the northern midlatitudes by changes in cirrus is predicted to be low, namely <1% of the intended radiative forcing by the stratospheric aerosols. This suggests that stratospheric sulphate geoengineering is unlikely to have large microphysical effects on the mean cirrus radiative forcing. However, this study disregards feedbacks, such as temperature and humidity changes in the upper troposphere, which must be examined separately. Key Points: Stratospheric geoengineering has not important side effect on cirrus clouds.